The Potency of Endophytic Bacteria Isolated From Red Ginger to Enhance Black Pepper Seedlings Growth - Andriana Kartikawati; NFN Gusmaini (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Endophytic bacteria have many benefits such as phosphate solubilization, nitrogen fixation, increasing mineral absorption as well as enhancing plant resistance against diseases. The research aimed to obtain endophytic bacteria potential to stimulate the growth of black pepper seedling. The first step was isolating endophytic bacteria from roots, rhizomes, and leaves of healthy red ginger. Characterization and selection were conducted by evaluating the capability on phosphate solubilization, nitrogen fixation, and indole acetic acid (IAA) hormone production of the isolated endophytic bacteria. There were 36 isolates consisted of 14 isolates from leaves, 9 isolates from roots and 13 isolates from rhizomes. Seventeen isolates were capable to dissolve phosphate, fix nitrogen and produce IAA or possessing those three characters, but only nine isolates were tested on pepper seedlings. The nine isolates were Ajc 1, Ajc 3, Ajc 7, Ajc 9, Rjc 1, Rjc 6, Djc 3, Djc 6, and Djc 11. Further evaluation of the nine isolates which were inoculated to pepper seedlings, indicated that Rjc1 isolate enhanced pepper seedlings height better than other isolates.